One-loop divergences in 6D, NN = (1, 0) SYM theory; Journal of High Energy Physics; Vol. 2017 - Bukhbinder I. L. Iosif Lvovich; Ivanov E. A. Evgeny Alekseevich; Merzlikin B. S. Boris Sergeevich; Stepanjyants K. V. Konstantin Viktorovich (2017, 2017)
Title screen